Tools for Knowledge and Learning: A Guide for Development and Humanita rian Organisations - Ramalingam, Ben (ODI, 2006)
This toolkit presents entry points and references to the wide range of tools and methods that have been used to facilitate improved knowledg e and learning in the development and humanitarian sectors.